2016
DOI: 10.3892/ijo.2016.3447
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of long non-coding RNA-CTD903 inhibits colorectal cancer invasion and migration by repressing Wnt/β-catenin signaling and predicts favorable prognosis

Abstract: Abstract. Accumulating evidence reveals that long non-coding RNA (lncRNA) is essential for tumorigenesis and progression, but little is known about its roles and mechanisms in metastatic colorectal cancer (CRC). This study aimed to detect expression level and prognostic role of lncRNA-CTD903 in CRC patients, which was selected based on one microarray data. The effects on cell invasion, migration and proliferation were investigated after silencing or overexpression of CTD903 in CRC cell lines. We also observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 34 publications
1
57
0
Order By: Relevance
“…There is currently no evidence showing the direct targeting of ZO-1 by Twist1. However, emerging evidence showing that repression of ZO-1 expression in cancer cells during EMT involves transcription factors including Twist14950. Consistently, our REST overexpression data showed that overexpression of REST in CWR22Rv1 cells significantly reduced Twist1 and N-cadherin expression, along with increased ZO-1 level (Figs 4A and 5A).…”
Section: Discussionsupporting
confidence: 83%
“…There is currently no evidence showing the direct targeting of ZO-1 by Twist1. However, emerging evidence showing that repression of ZO-1 expression in cancer cells during EMT involves transcription factors including Twist14950. Consistently, our REST overexpression data showed that overexpression of REST in CWR22Rv1 cells significantly reduced Twist1 and N-cadherin expression, along with increased ZO-1 level (Figs 4A and 5A).…”
Section: Discussionsupporting
confidence: 83%
“…β-catenin is a proliferation-related transcription factor. However, its effects on tumor invasion and EMT have been gradually recognized [27]. E-cadherin repressor Snail or Slug is also activated by β-catenin–Lefs/Tcfs-mediated transcription [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CCAT2 [7], H19 [129], CASC11 [134], TINCR [111], CCAL [128], cir-ITCH [82], and CTD903 [135] are involved in the WNT pathway, which also regulates gene expression changes during EMT[111]. WNT signaling can promote cancer progression-associated EMT processes via β-catenin-mediated increased gene expression at the invasive front of colorectal tumors [136].…”
Section: Lncrnas Involved In the Invasion Metastasis Early Diagnosimentioning
confidence: 99%